Funkcjonalne związki rynku wewnętrznego z produkcją w modelu mieszanym - Kramer, Teodor (Wydział Prawa i Administracji UAM, 1968)
A correct system of the production connections with the home market is, when a proper structure of supply from the point of view of the individual consumer is defined by the quick flow of the information from the consumer to the producer. In analysing the actual system of market connections with production, it has been stated, that in the connection market—producer, disturbances appear, stemming from extension of the direction of the information flow and from the fact that production reacts only indirectly in retail order. Extension of the direction of information flow appears in the first place on the sector consumer — production, considering the fact, that there is a mediation of the institutional wholesale in state-owned trade. Market information flow from the consumer to the wholesale, where it is aggregated and transmitted not earlier than now, further to the production and central planificator. Extension of the way of the market information flow and its transformation by wholesale, causes it to be useless for current decision about market structure. In actual market model in Poland contradiction appers between the consumer request and production structure. This contradiction is not yet solved by market methods. Institutions producing for the needs of the home market have to obey many directive indicators comming from central planificator. These directives concern the value of the marchandise production, financial indicators, investments and funds of payment. Detailed directives from higher authorities limit independent action of the concern. This is a further cause which makes more difficult an elastic reaction of the producer on the market order. Besides these, cause appear such as: stock deficit, shortage of the appropriate machines and appliances and improper system of the production planning for need of the market. Fuction of the national economy contains many contradictions, considering the fact, that both formations are superimposed: market formation with respectively self-acting regulation and plan formation with dictation type of the regulation. Deficiency of an elaborate system coupling both these formations is the principle cause of contradictions which arrise between production and home market.
Functional Connections of Home Market and Production in a Composite Model